Cassius Dio - Lange, Carsten Hjort (Historiography of Rome and Its Empire Ser, 2020)
Intro -- Contents -- Notes on Contributors -- Cassius Dio: Between War and Civil War -- Part 1 Violence -- Chapter 1 Violence as an Interpretive Category in Cassius Dio: The Terror under Sulla in 82 BCE -- Chapter 2 Gossip of Violence and Violence of Gossip: Livia's Lament and Its Remedy in Cassius Dio's Severan Context -- Part 2 War -- Chapter 3 Causation and Morality: Cassius Dio on the Origins of Rome's External Wars under the Republic -- Chapter 4 Caesar's Campaigns in Cassius Dio's Late Republic -- Chapter 5 Cassius Dio and the Roman Empire: the Impact of the Severan Wars on Dio's Narrative -- Chapter 6 "A Warlike Man": Cassius Dio's Perception and Interpretation of the Imperial Military persona -- Part 3 Civil War and the City of Rome -- Chapter 7 The War Comes Home: Rome and Romans during Civil Conflict in the Roman History -- Chapter 8 Talking Heads: the Rostra as a Conspicuous Civil War Monument -- Part 4 Civil War and the Senate -- Chapter 9 Cassius Dio, Cicero, and the Complexity of Civil War -- Chapter 10 Cassius Dio on Senatorial Activities as a Factor of Political Instability and Civil War -- Chapter 11 Cassius Dio and Senatorial Memory of Civil War inthe 190s -- Part 5 Civil War and the Severans -- Chapter 12 Cassius Dio, Ὁμόνοια, and Civil War -- Chapter 14 Civil War and Governmental Change: From the Achievements of Augustus to the Failures of the Severans -- Index.